2019
DOI: 10.1186/s12865-019-0300-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal immunosequencing in healthy people reveals persistent T cell receptors rich in highly public receptors

Abstract: Background The adaptive immune system maintains a diversity of T cells capable of recognizing a broad array of antigens. Each T cell’s specificity for antigens is determined by its T cell receptors (TCRs), which together across all T cells form a repertoire of millions of unique receptors in each individual. Although many studies have examined how TCR repertoires change in response to disease or drugs, few have explored the temporal dynamics of the TCR repertoire in healthy individuals. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
71
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 46 publications
6
71
0
Order By: Relevance
“…Most previous studies focused on TCR beta repertoires, partially because the diversity of TCR beta is higher, making it a better marker for clonal tracking [39]. We found that TCR alpha may be used for clonal track-ing as well, giving almost the same results as TCR beta in terms of the number of expanding clonotypes and their cumulative fractions on different timepoints.…”
Section: Discussionmentioning
confidence: 63%
“…Most previous studies focused on TCR beta repertoires, partially because the diversity of TCR beta is higher, making it a better marker for clonal tracking [39]. We found that TCR alpha may be used for clonal track-ing as well, giving almost the same results as TCR beta in terms of the number of expanding clonotypes and their cumulative fractions on different timepoints.…”
Section: Discussionmentioning
confidence: 63%
“…The proposed framework is not limited to identifying a response during an acute infection, but can also be used as method for learning the dynamics from time dependent data even in the absence of an external stimulus [19]. Here we specifically assumed expansion dynamics with strong selection.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has demonstrated the potential to identify particular receptors involved in the immune response, offering an alternative to in vitro binding or functional assays [15,16] or to RepSeq studies of cohorts with a common condition [17]. The natural temporal evolution of TCR repertoires has also been studied as a function of age across healthy individuals [18] or across time in single healthy individuals [19]. While these experiments yield a wealth of data, it is not always clear how to process and analyse them, or to link them to existing models of lymphocyte dynamics and proliferation [20][21][22][23].…”
mentioning
confidence: 99%
“…The distribution of peripheral lymphocyte subsets reflects the immune status and is correlated with survival in SCLC . Further, the specificity of each T cell for antigens is determined by its T‐cell receptors (TCRs), which together across all T cells form a repertoire of millions of unique receptors in each individual . TCR diversity is predominantly derived from the highly variable complementarity‐determining region 3 (CDR3) and is generated by random rearrangement and junction region mutation of the V‐D‐J regions, which are three fragments located in TCR‐coding genes.…”
Section: Introductionmentioning
confidence: 99%
“…13 Further, the specificity of each T cell for antigens is determined by its T-cell receptors (TCRs), which together across all T cells form a repertoire of millions of unique receptors in each individual. 14 TCR diversity is predominantly derived from the highly variable complementaritydetermining region 3 (CDR3) and is generated by random rearrangement and junction region mutation of the V-D-J regions, which are three fragments located in TCR-coding genes. Many studies have shown that lymphocytes recognize the patient's unique mutations in the peripheral blood 15,16 ; TCR repertoire in peripheral blood could be a biomarker of clinical outcomes for chemotherapy and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%